Arching Patterns in Three Dimensions of Sand Under Vertically Vibrated - Chaiworn, Panupat; Thepha, Panutta (Naresuan University Journal: Science and Technology (NUJST); Vol 28 No 2 (2020): April-June 2020DO - 10.14456/nujst.2020.12, 2020)
This research studied the arching patterns of sand in 3D under vertical vibration by considering the vibration conditions such as frequency, amplitude and the dimensionless vibration acceleration. In addition, the mechanism of the system from video recording and object tracking was analyzed. It was found that the frequency and amplitude of the vibrator were set in vertically.Cymatics was described the science of wave phenomena of vibration wave forces.In this experiment the source of sound was connected via a wave driver to the acrylic plate with fine sand strewn on it. Found that, the arching patterns were observed using square plates for frequency 150-180 Hz (grille pattern) and lower 100-140 Hz (corner pattern) and higher octaves 200-250 Hz (concave square pattern). However, the arching patterns are dependent on the dimensions of the plate, and it may be noted that these are kept constant and not varied while conducting the experiments.The variation was consistent. When the frequency was increased, the amplitude decreased. It demonstrated that the lower the system vibration was, the lower the amplitude would be. The Arching patterns of sand depended on the frequency, amplitude and the dimensionless vibration acceleration divided into 3 types: corner, grille and concave square. Keywords: Archingpatterns, Sand, Vertical vibration, Thedimensionless vibration acceleration